Analisis Sentimen Temporal Tentang Kuliner Di Kota Surabaya Berbasis Gender Menggunakan Bahasa Indonesia - Asmara, Rengga; Basuki, Achmad; Al Rasyid, Muhammad Udin Harun (Technomedia Journal, 2020)
Surabaya is the capital city of East Java Province, Indonesia, and the largest metropolitan city in the province. Surabaya is the largest city in Indonesia after Jakarta. With its large area and a fairly dense population, the city of Surabaya has a variety of culinary to offer. This culinary diversity attracts responses and opinions from the public (both positive and negative). People have certain ways to express their opinions, including through social media. Opinions shared by the Indonesians about Surabaya’s culinary in social media provide the right step to know what people think about the culinary places in Surabaya. But these opinions are very diverse because social media does not decide what people will say. We need opinion analysis to gain uses information from those opinions. In this research, we offered a new approach in analyzing the opinion on the culinary places in Surabaya using temporal analysis based opinion mining. The source is the opinions expressed in Foursquare using Indonesian. The rate of the accuracy is still around 67.32%, because other than Indonesian as the formal language used in the express opinions, social media users there also use many local dialects and slangs.